Optimizing Soil Fertility To Achieve Food Security In Krueng Raya, Aceh Besar District - Eka Sri Wulandari; Helmi Hasan Basri (International Journal of Multidisciplinary Sciences and Arts, 2026)
Agroforestry optimizes soil fertility by adding organic matter from tree litter, enhancing nutrient cycling, improving soil structure and water-holding capacity—all of which contribute to increased and stable crop yields, thereby supporting food security. Soil fertility optimization is the process of improving soil quality to make it more productive and support plant growth, including   which can be achieved through soil and water management techniques in agroforestry systems, beginning with periodic soil analysis to help determine plant nutrient needs and assist in establishing appropriate fertilization strategies. Soil fertility in agroforestry lands is crucial for supporting food security. Agroforestry, which involves the integration of trees with agricultural crops, can significantly enhance soil fertility through various mechanisms. The objective of this study is to analyze the soil in agroforestry lands regarding its physical and chemical properties, as well as to develop agroforestry-based land optimization strategies. The results indicate that the soil texture in Mon Village is loamy. Its chemical properties include slightly acidic soil (pH), low organic carbon (C-Organic), low total nitrogen (N-total), very low available phosphorus (P-available), and high soluble potassium (K-dd). The key factors determining the success of land optimization include: (a) Ecological aspects, such as the types of trees planted and soil fertility (i.e., soil physical and chemical properties), (b) economic aspects, including farmers’ knowledge of economic value, and (3) socio-cultural aspects, including community perception and participation, understanding of agroforestry systems, and the local wisdom of communities surrounding the forest.